The Role of E-Catalog as a Service Innovation in Enhancing Government Procurement and Empowering MSMEs: A Literature Review - Nugroho, Dwi Sofyan (KnE Social Sciences, 2025)
The digitalization of public services drives the government to develop a more transparent, efficient, and accountable system for goods and services procurement through the e-catalog platform. This study aims to examine conceptually and empirically the role of e-catalog as an innovative tool in enhancing the quality of government procurement services and its impact on empowering MSMEs. The method used is a literature review of relevant national journals and conference proceedings. The findings show that the implementation of the e-catalog accelerates procurement processes, shortens distribution chains, and broadens market access for MSMEs. However, challenges such as limited access to information, digital literacy, and production capacity remain obstacles to optimal MSME participation. Therefore, the e-catalog needs to be strengthened with affirmative policies, technical training, and capital support to prepare MSME actors to compete in the digital procurement system.